Biological Dynamics of a Polish Rural Community in The XIX Century. II. System of Mating and Fertility - Henneberg, Maciej (Anthropological Review, 1977)
The paper presents a part (concerning marriages and fertility) of the study undertaken within the Biological History of Human Populations Research Program on the data derived from the registers of Szczepanowo parish (situated in the northern part of Central Poland). The general aim of the study is to obtain information on changes in gene pools of the Polish populace occurring in the period of socio-economic change in this part of Poland. The general demographical characteristics of the parish have been presented in the earlier paper (Henneberg 19772). On grounds of this characteristics, it may be concluded that the region of Szczepanowo was inhabited by a group of people being a sample representative for the 19th-century Great Poland rural populace. This paper gives detailed information on marriages and fertility based on the analysis of age, place of origin, and previous marital status of spouses and intervals between births. Average age of spouses with regard to their sex and previous marital status (maids, bachelors, widowed) is presented in table 1. The age at marriage in Szczepanowo parish was similar to that observed in Poland in the years 1931 - 59. Correlation of bride's and bridegroom's ages though statistically significant is relatively weak (see table 3-4). Although the populace of Szczepanowo parish was in principle exclusively monogamic (Roman Catholics), there was a high amount of "biological polygamy" due to remarriages of widowed persons. The index of polygamy — Rp — calculated as a number of marriages contracted by an average person from the group is clearly higher than 1.0 (see table 5) showing increased, in comparison with absolute monogamy, possibility for various genome recombinations. From the analysis of marital distances, it follows that the migration (in the terms of gene exchange among groups inhabiting separate settlements) was intense and isotropic. The distribution of marital distances fits closely predictions from the model of two-dimensional isotropic permanent migration (Henneberg 1976, 1978). For numerical characteristics of marital distances distribution and related information see tables 6-10 and fig. 1-8. The level of endogamy in the investigated region was during the 19th century similar to that found in parishes of England and New England in the 18th - 19th century. The analysis of fertility is based on observation of protogenetic and intergenetic intervals. Parameters of birth spacing (in months) with respect to parity and age of women are given in tables 10 - 15. The duration of proto- and intergenetic intervals in Szczepanowo parish is similar to that found in Western Europe previous to widespread use of contraceptive techniques. From the duration of birth intervals combined with additional information on the proportion of unmarried and prematurely sterile persons, there are estimated age-specific birth rates (table 18). These rates fall within the range defined by respective rates for various historical and modern non-Malthusian populations. The shape of fertility function as measured by the age-specific relative cumulative number of births is in the investigated region typical for non-Malthusian populations (see fig. 12).